Students' Perception of Using Quizizz Gamification for English learning in Islamic Education - Hasanah, Nur (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Gamification, or the use of game qualities outside of a game setting to influence learning-related behaviors or attitudes, is seen as a novel approach to meeting the various requirements of students with learning or behavioral issues. Quizizz, a game-based online exam that enables engaging multiplayer teaching activities and allows learners to practice with their devices, is one of the most popular digital educational games. The purpose of this study was to find out how Quizizz, a formative assessment tool, was perceived by students at the